STRUKTUR FOLKLOR DALAM TRADISI ANTAR AJONG PADA MASYARAKAT MELAYU SAMBAS - Nurul Lisa; Ahadi Sulissusiawan; Agus Syahrani (Universitas Tanjungpura, 2020)
AbstrackThis research aimed to know about the intrinsic structure of folklore, the physical structure of the spells, and the structure of the expression of the prohibition of people's beliefs. The method used in this research was descriptive method. The data source in this study was the people's prose stories, spells, and expressions of the prohibition of people's beliefs in the antar ajong tradition which are told from informants from Desa Tanah Hitam. Data collection techniques used were document study and interviews. The conclusion that folklore has a character that can’t be separated from the King, the plot used is the forward plot, the setting is a place, time, and social setting. The diction contained in the spell consisted of 28 lines. There are 16 lines of auditive images, 5 lines of visual images, and 2 lines of tactile images. The concrete word contained in the spell consisted of 6 lines, while there are 4 lines of metaphorical figure of speech and 1 personification of figure of speech. The expression of the prohibition of popular belief consists of 3 two-part structures and 2 three-part structures. Keywords: antar ajong, folklore, structure, tradition.